The curse of a size: socio-cultural conception of dwarfism and effects on political participation in south-western Nigeria - Olaniyan, Azeez Olusola (The Center for Disability Studies and Services Brawijaya University, 2019)
The notion of dwarfs as inferior members of the society is a long-held belief amongst the Yoruba ethnic group of south-western Nigeria. By virtue of their size, dwarfs are objects of amusements and ridicule and denied political and leadership opportunities. They cannot become kings, hold chieftaincy titles; serve as heads of family, village heads or occupy leadership positions. In spite of persistence of this discrimination, there is a dearth of research on dwarfs' socio-political life. And this raises some pertinent questions: what is the socio-historical conception of dwarfism among the Yoruba people? What are the socio-cultural barriers placed on the dwarfs? What are the effects of these on dwarfs' psycho-political participation as members of the society? And, how do they express their socio-psychological and political affinities, affiliations, preferences, and feelings? Using participant observation, in depth interviews with key informants and archival search, this study seeks to interrogate these problematic.